COLLECTIVE FARMS IN THE WORKS OF A.N. CHELINTSEV AND N.P. MAKAROV (1951-1966) - А М Никулин; И В Троцук (RUDN journal of Sociology, 2017)
The article presents a part of the intellectual legacy of the Chayanov’s school that is often con-sidered as consisting exclusively of the studies of peasant economy and its cooperative development. Such an interpretation overlooks the school’s contribution to the study of large-scale agrarian production within the establishing soviet system of collective farms. The authors provide another interpretation of the intellectual legacy of Chayanov and his colleagues, and focus on the works of A.N. Chelintsev (1874-1962) and N.P. Makarov (1888-1980), who survived the repressions of the 1930s and since the 1940s returned to the studies of economic organization of collective farms, which had become the main insti-tutional form of the soviet agrarian system. Chelintsev studied lagging collective farms, which were un-popular and even dangerous subject in the soviet agrarian science. Chelintsev’s recommendations were not followed in the collective farms’ economy of the 1950s. However, today they help to understand some system features of weak collective farms. Makarov summarized the results of his collective farms studies at the rise of the Kosygin’s reforms in the monograph published in 1966; it emphasized both the importance of collective farms in the soviet agriculture and alternative strategies of collective farms develop-ment by granting them more independence and involving in inter-farm cooperation. With such works, Chelintsev and Makarov ensured the highest methodological level of social-economic research typical for the 1920s’ soviet agrarian science, thus confirming that the Chayanov’s school introduced many original ideas in the study of peculiarities of the economic organization of both peasant households and large-scale collective farms, which determines the necessity of reevaluating the intellectual legacy of the organizational-production school to understand better the phenomenon of Russian collective farming in the XX century.